Efficacy and Safety of Triple Synergy Therapy Containing Annona Senegalese, Ciprofloxacin, and Omeprazole for Helicobacter Pylori Initial Treatment - Umaru, Isaac John; Akafa, Tensaba Andes; Ngbede, Ocheifa Matthew; John, Artu Ishishen; Umaru, Kerenhappuch Isaac (African Journal of Clinical Medicine and Pharmacy Research, 2025)
Annona senegalensis is a complex plant, with several active compounds contributing to its medicinal properties. The presence of alkaloids such as annonaine and corossolin, which have been shown to possess anti-inflammatory and analgesic effects, is particularly noteworthy. Flavonoids like quercetin and kaempferol are potent antioxidants that help to reduce oxidative stress, while tannins contribute to the plant’s antimicrobial and anti-inflammatory properties. These compounds, working synergistically, may explain the plant’s potential. Material and methods: This study was conducted in accordance with the Declaration of Helsinki with little modification, The rats were completely randomized, numbered according to the sequence, and randomly enrolled in a ratio of 1:1:1 to receive the triple therapy (A group, Annona senegalensis, ciprofloxacin quadruple therapy (B group as Omeprazole quadruple therapy. Results: Annona Senegalese scheme for initial and rescue treatment of H. pylori infection are not inferior to the guideline-recommended therapy. A study compared the eradication efficacy of the Annona Senegalese quadruple therapy (300 mg, 3 times/day) with that of bismuth quadruple therapy. The eradication rates of H.pylori were 87.5% and 87.1% in PP analysis, with no statistical significance (P >0.05), It was observed that, the eradication rates of H. pylori in response to the new triple therapy consisting of Annona Senegalese’s triple therapy (A. Senegalese 500 mg, Ciprofloxacin 1000 mg, Omeprazole 20 mg, A group), were 70.0% and 81.4% by ITT and PP analyses, respectively. Conclusion: The efficacy of Annona Senegalese triple therapy for the initial eradication of H. pylori is commendable thus be used as a combination in clinical therapy.